Erenumab for Migraine Prevention in a 1-Year Compassionate Use Program: Efficacy, Tolerability, and Differences Between Clinical Phenotypes - Schoenen, Jean; Timmermans, Gregory; Nonis, Romain; Manise, Maïté; Fumal, Arnaud; Gérard, Pascale (Frontiers in Neurology, 2021)
During a 1-year compassionate use program, 156 migraine patients self-administered a monthly dose of erenumab 140mg with a subcutaneous auto-injector. Main inclusion criteria were: ≥ 4 migraine days/month and ≥ 2 prior prophylactic treatment failures. The patients covered the migraine severity spectrum from episodic (EM, n=80) to chronic migraine (CM, n=76). During the 3rd month of treatment, monthly headache days decreased by 45.7% in EM, by 35.5% in CM. The 50% responder rate for reduction in monthly headache days was significantly higher in EM (55%) than in CM (43%, p=0.05). Mean headache severity, duration and monthly days with acute drug intake were also significantly reduced. 54.1% of CM patients reversed to EM. The therapeutic effect was maintained at 12 months when 50% responder rates still were 51% in EM and 41% in CM. Ten EM patients and 23 CM patients had discontinued treatment, considering the treatment as ineffective. At month 3, 48% of patients reported non-serious adverse events among which the most frequent was constipation (20.5%). Discontinuation due to an adverse effect for the entire 12-month period was rare (3.8%). The lower efficacy in CM than in EM was due to a very low 50% responder rate in CM patients with continuous pain (13%) as compared to CM with pain-free periods (58%, p<0.001). Similarly, the 50% responder rate was lower in patients with ≥ 2 prior prophylactic treatment failures (40.5%) compared to those with 2 failures (70%, p<0.05). There was no significant efficacy difference between low and high frequency EM, nor between CM patients with (n=50) or without (n=26) acute medication overuse. Erenumab had no effect on the frequency of auras. Taken together, erenumab 140mg monthly was highly effective for migraine prophylaxis over the whole severity spectrum of the disease, except in patients with continuous headaches. Its effect is significant after the 1st injection, quasi maximal after the 2nd injection, and does not wear off after 12 months. The most frequent adverse effect was constipation. These results are compared to those published for erenumab in the pivotal randomized placebo-controlled trials and to those reported in several recent real-world studies.